Komunikasi Pemasaran Digital Mills melalui Brand Ambassador Bambang Bayu Saptaji di Instagram - Suhandi, M Akmal; Nurhanifah (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
This study aims to analyze the forms of digital marketing communication messages and the role of a brand ambassador in delivering these messages through Brand Mills’ Instagram content. This research uses a qualitative approach with content analysis methods on posts featuring Bambang Bayu Saptaji. Data collection techniques include non-participant observation and documentation, while data analysis involves data reduction, data presentation, and conclusion drawing. The results show that two types of marketing communication messages are used: informative and persuasive. Informative messages aim to provide audiences with an understanding of product characteristics, concepts, and advantages, while persuasive messages are used to attract attention and influence audience attitudes. Furthermore, the brand ambassador plays a significant role in enhancing the credibility of information and strengthening the attractiveness and influence of the messages delivered. Therefore, the use of a brand ambassador is an effective strategy in digital marketing communication to increase audience understanding and interest in the product.